An induction-based compaction of sets of association rules among web concepts - Minuto Espil, Mauricio; Ale, Juan María (2010)
Association rules are nowadays regarded as robust vehicles for creating Web recommendations. We present an induction-based technique for creating a compact representation of sets of association rules, particularly intended for publishing the compact representation in the Web. Our technique efficiently induces a defeasible logic program from a set of association rules, in a manner that the complete set of the given associations can be concluded, when integrating the induced compact program within a defeasible logic reasoning framework.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
International Conference on Research Challenges in Information Science (4ª : 2010 may. 19-21 : Niza, Francia). IEEE, 2010, pp. 311-318
Keywords: REGLAS DE ASOCIACIÓN; ONTOLOGÍAS; MINERÍA DE DATOS; PROGRAMACIÓN LÓGICA